Potential trends in invasion risk of the yellow-legged hornet, Vespa velutina, in Ukraine - Tytar, V.M.; Kozynenko, I.I. (Доповіді НАН України, 2023)
In the recent decade an alarming problem has risen about the invasion of Vespa velutina Lepeletier, 1836 (Hymenoptera:
Vespidae) in European ecosystems. The species can cause serious damage to ecosystem biodiversity and in
areas where it has been introduced, and can have serious impacts over beekeeping. Bioclimatic modelling suggests
that under current climate conditions representatives of the invasive species have chances in the near term to invade
a number of regions in Ukraine, especially in the west of the country, including Transcarpathia, and Crimea. Under
predicted climate change the hornet will most likely extend its presence in Ukraine. В останнє десятиліття виникла серйозна проблема щодо інвазії Vespa velutina Lepeletier, 1836 (Hymenoptera:
Vespidae) в екосистеми Європи. Вид може завдати істотної шкоди біорізноманіттю екосистем у районах, де він був інтродукований, а також негативно вплинути на бджільництво. Біокліматичне моделювання свідчить про те, що за сучасних кліматичних умов представники виду мають шанси найближчим часом
з’явитися у низці областей України, особливо на заході країни, у тому числі Закарпатті, та в Криму. За прогнозованих змін клімату шершень, найімовірніше, продовжить поширюватися в Україні.